The water quality of the Lupar and AI river systems (Sarawak, Malaysian Borneo) in light of increasing anthropogenic activity and the social implications - Herbert, Richard; Lohan, Maeve; Zainudin, Zaki (International Water Association, 2010)
Historically, populations across Malaysia settled next to rivers in order to provide and safeguard essential goods and services such as a source of drinking water, protein food resources, areas for washing, sanitation and transportation. Settlements along the Lupar and Ai rivers (Figure 1) are no exception, and have retained a high level of dependence on river ecosystems to provide these goods and services to varying degrees. Changes in land use and development in the river basin has caused adverse affects on the river water quality. The study will provide a tool for planning, development and infrastructure reviews in the region, and essentially an ecosystem based approach to river basin management (RBM).